KEBERTAHANAN MATERIAL VERNAKULAR DI DESA ADAT BAYUNG GEDE : ANTARA TRADISI DAN MODERNISASI - SUPARSA, TJOKORDA GEDE DALEM; MASADI, SAKINA; YASAPUTRA, I MADE AGUNG SADHANA; NDAKULARAK, KRISANDY; DIVAWIPRAYASA, GEDE ADITYA; PERMANA, I KADEK AGUS (Ganec Swara, 2025)
Bayung Gede Village is one of the Bali Mula Villages that has preserved its vernacular architecture through the use of natural materials such as bamboo, timber, and stone. However, modernism has caused a shift in material preferences, potentially threatening the identity of traditional architecture. This research aims not only to analyse the pattern of vernacular material use but also to identify strategies applied by the people of Bayung Gede to sustain their architectural heritage amid economic and social changes. The research employs a descriptive-qualitative method and a case study approach, including observations, in-depth interviews, and literature review. The results show that villagers tend to prefer modern materials for construction due to considerations of durability, cost efficiency, and accessibility. However, efforts to preserve traditional architecture remain, particularly through a Neo-Vernacular approach that integrates modern materials with traditional design principles. In conclusion, the sustainability of vernacular architecture in Bayung Gede depends on appropriate regulations, education, and incentives for villagers, such as developing the village into a "Desa Wisata" (tourism village) based on vernacular architecture.